An Investigation of Master Student Understanding on Mathematical Literacy Problems - Al Jupri; Rizky Rosjanuardi (Universitas Maritim Raja Ali Haji, 2020)
Indonesian government has been promoting the National Literacy Movement since 2016 to response disappointing results of the Program for International Student Assessment on literacy and mathematical literacy skills of students. This movement involves many parties, including educational universities, to prepare mathematics education students of master level, as prospective teachers or lecturers, to understand mathematical literacy. To investigate this condition, this study aims to analyze master student understanding on mathematical literacy problems. To do so, we conducted an online survey via Google Form involving 32 master students from several universities in Bandung. In this survey, each master student was called for sending two mathematics problems and solutions that considered to be literacy problems. The results revealed that 17 (53%) involved master students understand mathematical literacy problems. The most frequent category of literacy problems to appear was Change and Relationship followed by categories of Space and Shape, Uncertainty and Data, and Quantity, respectively. Another result showed that word problems seemed to be regarded as the same as mathematical literacy problems by some students. We conclude that master student understanding of mathematical literacy needs to be improved for facing future educational careers.